Effects of causality constraints on Bayesian analysis of heavy-ion collisions - Domingues, Thiago Siqueira (2024)
There have long been questions about the limits of validity of relativistic hydrodynamics, and whether it is being used outside its regime of validity in modern simulations of relativistic heavy-ion collisions. An important new tool for answering this question is a causality analysis if the evolution equations do not respect relativistic causality, they are not a faithful representation of the underlying theory (in this case, quantum chromodynamics). Using this criterion, it has recently been shown that hydrodynamics is indeed being used outside its regime of validity, at least sometimes. Here we explore the phenomenological implications, particularly the quantitative effects of demanding limits on acausality in modern Bayesian parameter estimation. We find that, while typically only a small fraction of the systems energy is initially in an acausal regime, placing strict limits on the allowed energy fraction significantly changes the preferred properties of the initial condition, which in turn alters the extracted medium properties such as bulk viscosity.